Pengaruh Pengetahuan Keselamatan dan Kesehatan Kerja (K3) terhadap Perilaku Penggunaan Alat Listrik Kecantikan pada Mahasiswa Tata Rias Universitas Negeri Jakarta: Penelitian - Nashwa Karinta Dilla Prasaja; Elvyra Yulia; Dwi Atmanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aimed to examine the effect of Occupational Health and Safety (OHS) knowledge on the behavior of using electrical beauty devices among students of the Beauty Education Study Program at Universitas Negeri Jakarta. A quantitative approach was employed using survey and test methods. The sample consisted of 64 students selected through purposive sampling, with criteria including completion of OHS-related courses and experience in using electrical beauty devices. Data were collected using an OHS knowledge test and a questionnaire measuring safe behavior in the use of electrical beauty devices, both of which had passed validity and reliability testing. Data analysis was conducted using simple linear regression with SPSS version 25. The results indicated that OHS knowledge had a positive and significant effect on the behavior of using electrical beauty devices, as shown by a t-value of 3.246, which exceeded the t-table value of 1.999, and a significance level of 0.002 (p < 0.05). The regression coefficient of 1.090 suggested that each one-unit increase in OHS knowledge was associated with an improvement in safe and appropriate usage behavior of electrical beauty devices. These findings highlighted the importance of strengthening OHS knowledge to promote safe work behavior among beauty education students.